Three Sabachay Gravestones - Damir V. Mukhetdinov (Археология евразийских степей, 2023)
The article deals with the project description of the gravestone of the outstanding theologian, orientalist and educator Khusain Faizkhanov (1823–1866), which was installed at the place of his burial in his native village of Safadjai, situated in the Pilna district of the Nizhny Novgorod region. Archival documents and memories of old residents of Kh. Faizkhanov's native village allowed to establish that the gravestone, installed after the scientist's death by his wife Fatima Faizkhanova, was soon destroyed by vandals and the grave itself was abandoned. In 1982, the imam-khatib of the 1st mosque in the village of Safadjai Abdulbari Allyamov made a fence around the grave, and in the autumn of 2000 Mansur Khakimov, a native of Safadjai, installed a new gravestone. On July 7, 2023, a new large monument, specially designed on the initiative of the Spiritual Administration of Muslims of the Russian Federation, was installed at the burial place of Kh. Faizkhanov. All aspects of Kh. Faizkhanov’s activity were taken into account and reflected during working out of its structural elements and their stylistic content. Additionally, the article considers the dating issue of his death. Various data, directly or indirectly reported by sources, are added, the points of view existing in scientific and reference works are analyzed. The proposed dates have discrepancies by one day. Careful attention to textual details in the works of Sh. Marjani allows the author to assert that his information should be recognized as accurate. Based on them, it should be considered that Kh. Faizkhanov died on the night of August 28-29, old style (or September 9-10, new style) 1866, on the night from Sunday of the Gregorian calendar to Monday of the Muslim calendar. The same information allows to consider that the time of birth of Kh. Faizkhanov in 1823 falls on the period not later than March 23.